METHODS AND ALGORITHM FOR COLOR METALLOGRAPHIC 3D IMAGES PROCESSING - Kornij, V. V. (International Journal of Computing, 2014)
The problem of processing of coloured 3D metallographic images in order to obtain the crack volume is considered. Method of 3D surface reconstruction is applied for crack volume estimation. The model of illumination image forming and algorithm of norm vector for horizontal cracks definition are developed. Formulas for crack volume estimation in the case of 3D reconstruction are presented.